2021
DOI: 10.1093/mnras/stab013
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the observability of population III stars with ELT-HARMONI via the helium 1640 Å emission line

Abstract: Population III (Pop. III) stars, as of yet, have not been detected, however as we move into the era of extremely large telescopes this is likely to change. One likely tracer for Pop. III stars is the He iiλ1640 emission line, which will be detectable by the HARMONI spectrograph on the European Extremely Large Telescope (ELT) over a broad range of redshifts (2 ≤ z ≤ 14). By post-processing galaxies from the cosmological, AMR-hydrodynamical simulation newhorizon with theoretical spectral energy distributions (SE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 76 publications
0
15
2
Order By: Relevance
“…However, the convex downward spectra of J1631+4426 and I Zw 18 NW suggest that contributions from stars to hard photons around 35.1 to 54.4 eV might not be as significant as expected in BPASS binary models. Stellar models including fast-rotating stars (e.g., Kubátová et al 2019) and population III stars (e.g., Grisdale et al 2021) also have convex upward spectra around 13.6 − 54.4 eV, unlike our results. These mismatches suggest that hard radiation from stellar sources cannot solely explain He ii ionizing photons for the two of our galaxies with convex downward spectrum shapes.…”
Section: Contributions From Stellar Radiationcontrasting
confidence: 99%
“…However, the convex downward spectra of J1631+4426 and I Zw 18 NW suggest that contributions from stars to hard photons around 35.1 to 54.4 eV might not be as significant as expected in BPASS binary models. Stellar models including fast-rotating stars (e.g., Kubátová et al 2019) and population III stars (e.g., Grisdale et al 2021) also have convex upward spectra around 13.6 − 54.4 eV, unlike our results. These mismatches suggest that hard radiation from stellar sources cannot solely explain He ii ionizing photons for the two of our galaxies with convex downward spectrum shapes.…”
Section: Contributions From Stellar Radiationcontrasting
confidence: 99%
“…Photometrically detected objects showing indicative Pop III color signatures may in principle be targeted for follow-up spectroscopyrendering the He II 𝜆1640 emission line detectable for sufficiently deep exposures. As shown in Grisdale et al (2021), Pop III galaxies with total stellar masses of ≥ 10 4 𝑀 , a top-heavy IMF and a compact stellar distribution would have a detectable He II 𝜆1640 emission line for redshifts 𝑧 = 4 − 10 with the HARMONI spectrograph on the ELT.…”
Section: Discussionmentioning
confidence: 89%
“…We emphasize that this does not mean that these are the only viable options for studying Pop III signatures in the early Universe. For example, Grisdale et al (2021) recently demonstrated the potential for detecting He II 𝜆1640 emission line from Pop III galaxies using the ground based ELT/HARMONI spectrograph. However, due to the small field of view of this instrument, the success of such an approach hinges on knowing where to point the ELT, as we have no a priori information on the location of Pop III galaxies on the sky 2 .…”
Section: Telescopes and Survey Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of the He 𝜆1640 line with Pop III stars has been pursued in the context of both targeted observations (e.g., Nagao et al 2005;Cai et al 2011;) and statistical measurements via the line-intensity mapping technique (e.g., Visbal et al 2015). While possible identifications have been made for objects such as "CR7" (Sobral et al 2015), the measurements are controversial and a solid He 𝜆1640 detection of Pop III stars may not be possible until the operation of next-generation ground-based telescopes such as the E-ELT (Grisdale et al 2021). A number of alternative (and often complementary) probes of Pop III stars have therefore been proposed, including long gamma-ray bursts (GRBs) associated with the explosive death of massive Pop III stars (Mészáros & Rees 2010;Toma et al 2011), caustic transits behind lensing clusters (Windhorst et al 2018), the cosmic near-infrared background (NIRB, Santos et al 2002;Kashlinsky et al 2004;Fernandez & Zaroubi 2013;Yang et al 2015;Helgason et al 2016;Kashlinsky et al 2018), and spectral signatures in the global 21-cm signal (Thomas & Zaroubi 2008;Fialkov et al 2014;Mirocha et al 2018;Mebane et al 2020) and 21-cm power spectrum (Fialkov et al 2013(Fialkov et al , 2014Qin et al 2021).…”
Section: Introductionmentioning
confidence: 99%